Psychometric properties of the performing arts module of the Disabilities of the Arm, Shoulder, and Hand questionnaire. Issue 24 (20th November 2018) - Baadjou, Vera; de Bie, Rob; Guptill, Christine; Smeets, Rob
Abstract: Background: The Disabilities of the Arm, Shoulder, and Hand questionnaire (DASH) offers an optional performing arts module. The goal was to examine the psychometric properties of this module in musicians. Methods: This study is a secondary analysis of a randomized controlled trial on the effectiveness of a biopsychosocial intervention to prevent or reduce playing-related disability in conservatory students. Baseline data were used to examine internal consistency and discriminative validity of the performing arts module of the DASH questionnaire. Construct validity was analyzed by hypotheses testing. The performing arts module outcomes were compared to scores from the general DASH questionnaire, pain disability index, Short-Form 36, playing-related musculoskeletal disorder (PRMD) intensity, and pain intensity. Results: Questionnaires completed by 130 conservatory students were analyzed, 55% of the population was female. Median age was 20 years (IQR 4). The performing arts module showed good internal consistency (Cronbach's alpha 0.893). Discriminative validity between students with and without PRMDs was good. Three out of six hypotheses were accepted, indicating moderate construct validity. Conclusions: The performing arts module showed good internal consistency, good discriminative validity and moderate construct validity in a population of conservatory students. Implications for Rehabilitation: Musicians suffer frequently from musculoskeletal disorders, mostly in the upper extremity. The Disabilities of the Arm, Shoulder, and Hand questionnaire is a well-known outcome measure, which also includes a performing arts module. This study is the first to explore psychometric properties of the performing arts module. The performing arts module of the Disabilities of the Arm, Shoulder, and Hand questionnaire showed good internal consistency, good discriminative validity, and moderate construct validity.